2021
DOI: 10.3389/fimmu.2021.653110
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Immunity Trained by Coronavirus Infections, DAMP Stimulations and Regulated by Anti-Oxidant NRF2 May Contribute to Inflammations, Myelopoiesis, COVID-19 Cytokine Storms and Thromboembolism

Abstract: To characterize transcriptomic changes in endothelial cells (ECs) infected by coronaviruses, and stimulated by DAMPs, the expressions of 1311 innate immune regulatomic genes (IGs) were examined in 28 EC microarray datasets with 7 monocyte datasets as controls. We made the following findings: The majority of IGs are upregulated in the first 12 hours post-infection (PI), and maintained until 48 hours PI in human microvascular EC infected by middle east respiratory syndrome-coronavirus (MERS-CoV) (an EC model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 175 publications
(203 reference statements)
1
90
0
Order By: Relevance
“…IL-21 receptor (IL21R) promotes inflammation in myocardial infarction [ 108 ] and respiratory disease [ 109 ]. CEACAM1 is a coronavirus receptor on endothelial cells as we reported [ 54 ] and promotes vascular aging process [ 110 ]. L1CAM regulates microRNAs associated with inflammation and progression of Alzheimer's disease and Parkinson's disease [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…IL-21 receptor (IL21R) promotes inflammation in myocardial infarction [ 108 ] and respiratory disease [ 109 ]. CEACAM1 is a coronavirus receptor on endothelial cells as we reported [ 54 ] and promotes vascular aging process [ 110 ]. L1CAM regulates microRNAs associated with inflammation and progression of Alzheimer's disease and Parkinson's disease [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our and others’ previous reports showed that human aortic endothelial cells (EC) are innate immune cells that have inflammasome/caspase-1 functions in sensing PAMPs and DAMPs [ 3 , 9 , 51 , 54 , 55 , 120 ]. However, several important questions remained: i) whether procaspase-1 or activated caspase-1 are localized in the nucleus in sensing nuclear DAMPs in HAECs during pyroptosis; ii) what the transcriptomic regulation functions of procaspase-1 in modulating inflammation if localized in the nucleus; iii) whether procaspase-1 has nuclear export signal; iv) whether procaspase-1 is activated in the nucleus after sensing conditional DAMPs; and v) whether procaspase-1 and/or activated caspase-1 have enzymatic activity-independent functions in the nucleus of HAECs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trained immunity can be beneficial for the host in terms of protection against heterologous infection, but dysregulated trained immunity response could result in pathological conditions as it was described in autoinflammatory diseases ( 48 , 49 ). A recent study has described induction of trained immunity by SARS-CoV-2 infection ( 50 ), and it has been proposed that this contributes to the acute dysregulation during the disease both an endothelial and immune cell level ( 51 ).…”
Section: Discussionmentioning
confidence: 99%